2022
DOI: 10.1111/bph.15932
|View full text |Cite
|
Sign up to set email alerts
|

The myeloid mineralocorticoid receptor regulates dermal angiogenesis and inflammation in glucocorticoid‐induced impaired wound healing

Abstract: Background and Purpose Delayed wound healing is among the deleterious consequences of over‐activation of the mineralocorticoid receptor (MR) induced by topical dermocorticoids. The role of dermal inflammation and angiogenesis in the benefits of MR blockade is unknown. Experimental Approach Skin wounds were made on C57Bl6 mice after topical pretreatment with the dermocorticoid clobetasol. The impact of topical MR blockade by canrenoate on inflammation, angiogenesis, and the wound macrophage phenotype was analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Whether the reduced cell infiltration results from the quicker restoration on the epithelial barrier or whether it is the primary effect of SPL cannot be determined; however, it confirms that SPL is released at an efficient concentration in the cornea as SPL did reduce IBA-1 positive cells in the rat model of laser-induced choroidal neovascularization [21] and in the diabetic retina [8]. Interestingly, in the glucocorticoid-impaired skin wound healing model, topical MR antagonists shorten the duration of inflammation by increasing the ratio of anti-inflammatory macrophages versus pro-inflammatory macrophages in wounds [35]. The role of activated and infiltrating dendritic cells in the healing process is complex and highly controlled since disrupted nerves can induce the activation of cells, which also interact with nerves to provide either protective or neurotoxic effects [36].…”
Section: Discussionmentioning
confidence: 86%
“…Whether the reduced cell infiltration results from the quicker restoration on the epithelial barrier or whether it is the primary effect of SPL cannot be determined; however, it confirms that SPL is released at an efficient concentration in the cornea as SPL did reduce IBA-1 positive cells in the rat model of laser-induced choroidal neovascularization [21] and in the diabetic retina [8]. Interestingly, in the glucocorticoid-impaired skin wound healing model, topical MR antagonists shorten the duration of inflammation by increasing the ratio of anti-inflammatory macrophages versus pro-inflammatory macrophages in wounds [35]. The role of activated and infiltrating dendritic cells in the healing process is complex and highly controlled since disrupted nerves can induce the activation of cells, which also interact with nerves to provide either protective or neurotoxic effects [36].…”
Section: Discussionmentioning
confidence: 86%
“…Immune cells are critical regulators of wound healing through the secretion of cytokines, lymphokines and growth factors 18 . Immune suppression induced by glucocorticoids showed delayed wound closure which resulted in impaired healing 3,19 . Patients who routinely take immunosuppressive medications have a significantly higher risk of postoperative wound dehiscence than normal people 5 .…”
Section: Discussionmentioning
confidence: 99%
“…18 Immune suppression induced by glucocorticoids showed delayed wound closure which resulted in impaired healing. 3,19 Patients who routinely take immunosuppressive medications have a significantly higher risk of postoperative wound dehiscence than normal people. 5 To address this problem, the use of drug suspending during wound healing has been suggested and was therefore explored in this study.…”
Section: Discussionmentioning
confidence: 99%
“…S5 ( 37 )). In humans, it has been shown that the GC-induced delay in wound reepithelialization can be prevented with the application of an MRA ( 54 ), which was attributed to reduced inflammation at the wound site ( 55 ).…”
Section: Discussionmentioning
confidence: 99%